Back to the bases: Building a terrestrial water δ18O baseline for archaeological studies in North Patagonia (Argentina). (20th May 2020) - Serna, Alejandro; Prates, Luciano; Valenzuela, Luciano O.; Salazar-García, Domingo C.
Abstract: Archaeology has been using stable oxygen as an isotopic tracer linked with water consumption for decades, and it has been demonstrated to be a powerful tool to assess paleomobility in bioarchaeology. Central-eastern North Patagonia (Argentina) is an especially appropriate region to apply it since it presents a high density of hunter-gatherer burials, it was a nodal zone criss-crossed by an extensive network of important routes, and it is characterized by a high environmental fragmentation due to the scarcity of fresh water sources. The aim of this paper is to build an empirical stable oxygen isotope baseline of terrestrial surface waters to assess the potentiality of tracing past human movement. We analyzed 46 water samples from 13 locations with permanent sources (rivers, springs, streams), compared it with predictions of precipitation and evaluated it considering seasonal variation, altitude and distance from the coast. Our results show that different post-precipitation processes change the isotopic signal from the sources with respect to the local precipitation, and highlight the relevance of analyzing terrestrial water sources. According to their oxygen isotope values we defined five hydrologic zones: Colorado River, Negro River, Closed Basins and Plains, Eastern and Western Somuncurá Foothills. Their identification shows the potential to address past human movement using stable oxygen water baselines in central-eastern North Patagonia.